1846 Sangaku Maximum

Geometry Level 5

Two unit squares, black and blue, are inscribed inside a trapezoid.

The black square shares a right angle corner and left side with the trapezoid. The blue square is rotated in such a way as to maximize the length of the vertical right side (purple) of the trapezoid.

This length can be expressed as 1 + a b c 1+\sqrt{a\sqrt{b} - c} , where a a , b b , and c c are square-free positive integers.

What is the sum a + b + c a+b+c ?


The answer is 37.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Guilherme Niedu
Feb 19, 2020

Let us define the tilting angle as x x and let us mark vertices A A , B B , C C , D D and E E as in figure below. Let us also call the purple side as y y .

We will have:

y = 1 + D E \large \displaystyle y = 1 + \overline{DE}

Notice also that:

B C = cos ( x ) + sin ( x ) 1 \large \displaystyle \overline{BC} = \cos(x) + \sin(x) - 1

A B = 1 + cos ( x ) \large \displaystyle \overline{AB} = 1 + \cos(x)

A D = cos ( x ) + sin ( x ) + 1 \large \displaystyle \overline{AD} = \cos(x) + \sin(x) + 1

Triangles Δ A B C \Delta ABC and Δ A D E \Delta ADE are similar, so:

D E B C = A D A B \large \displaystyle \frac{\overline{DE}}{\overline{BC}} = \frac{\overline{AD}}{\overline{AB}}

D E = ( cos ( x ) + sin ( x ) 1 ) ( cos ( x ) + sin ( x ) + 1 ) 1 + cos ( x ) \large \displaystyle \overline{DE} = \frac{ (\cos(x) + \sin(x) -1)(\cos(x) + \sin(x) + 1)}{1 + \cos(x)}

D E = ( cos ( x ) + sin ( x ) ) 2 1 1 + cos ( x ) \large \displaystyle \overline{DE} = \frac{ (\cos(x) + \sin(x))^2 - 1}{1 + \cos(x)}

D E = sin ( 2 x ) 1 + cos ( x ) \large \displaystyle \overline{DE} = \frac{ \sin(2x)}{1 + \cos(x)}

y = 1 + sin ( 2 x ) 1 + cos ( x ) \color{#20A900} \boxed { \large \displaystyle y = 1 + \frac{ \sin(2x)}{1 + \cos(x)} }

Differentiating y y with respect to x x and making it equal to 0 0 :

d y d x = 2 cos ( 2 x ) ( 1 + cos ( x ) ) sin ( 2 x ) ( sin ( x ) ) ( 1 + cos ( x ) ) 2 = 0 \large \displaystyle \frac{dy}{dx} = \frac{2\cos(2x) (1 + \cos(x)) - \sin(2x) ( -\sin(x) ) }{ (1+\cos(x))^2 } = 0

d y d x = 2 ( 2 cos 2 ( x ) 1 ) ( 1 + cos ( x ) ) + 2 sin 2 ( x ) cos ( x ) ( 1 + cos ( x ) ) 2 = 0 \large \displaystyle \frac{dy}{dx} = \frac{ 2 (2\cos^2(x)-1) (1 + \cos(x)) + 2\sin^2(x) \cos(x) }{ (1+\cos(x))^2 } = 0

d y d x = 2 ( 2 cos 2 ( x ) 1 ) ( 1 + cos ( x ) ) + 2 ( 1 cos 2 ( x ) ) cos ( x ) ( 1 + cos ( x ) ) 2 = 0 \large \displaystyle \frac{dy}{dx} = \frac{ 2 (2\cos^2(x)-1) (1 + \cos(x)) + 2( 1 - \cos^2(x) ) \cos(x) }{ (1+\cos(x))^2 } = 0

Since 0 x π 2 0 \leq x \leq \frac{\pi}{2} , 1 + cos ( x ) 0 1 + \cos(x) \neq 0 . So:

cos 3 ( x ) + 2 cos 2 ( x ) 1 = 0 \large \displaystyle \cos^3(x) +2\cos^2(x) -1 = 0

( cos ( x ) + 1 ) ( cos 2 ( x ) + cos ( x ) 1 ) = 0 \large \displaystyle (\cos(x) + 1)(\cos^2(x) + \cos(x) -1) = 0

cos ( x ) = 1 \cos(x) = -1 is impossible since 0 x π 2 0 \leq x \leq \frac{\pi}{2} . The other two solutions are cos ( x ) = 1 + 5 2 1.618 \cos(x) = - \frac{1 + \sqrt{5}}{2} \approx -1.618 , which is also impossible, and:

cos ( x ) = 5 1 2 \color{#20A900} \boxed { \large \displaystyle \cos(x) = \frac{ \sqrt{5} - 1}{2} }

Which leads to:

sin ( x ) = 2 5 2 2 \color{#20A900} \boxed { \large \displaystyle \sin(x) = \frac{ \sqrt{2\sqrt{5} - 2 }}{2} }

So:

y = 1 + sin ( 2 x ) 1 + cos ( x ) \large \displaystyle y = 1 + \frac{ \sin(2x)}{1 + \cos(x)}

y = 1 + 2 sin ( x ) cos ( x ) 1 + cos ( x ) \large \displaystyle y = 1 + \frac{ 2\sin(x)\cos(x)}{1 + \cos(x)}

y = 1 + ( 2 5 2 ) ( 5 1 ) 5 + 1 \large \displaystyle y = 1 + \frac{ \left ( \sqrt{2\sqrt{5} - 2} \right )(\sqrt{5} - 1)}{\sqrt{5} + 1}

Multiplying above and below by 5 1 \sqrt{5} - 1 :

y = 1 + ( 2 5 2 ) ( 6 2 5 ) 4 \large \displaystyle y = 1 + \frac{ \left ( \sqrt{2\sqrt{5} - 2} \right )(6 - 2\sqrt{5})}{4}

y = 1 + ( 2 5 2 ) ( 6 2 5 ) 2 4 \large \displaystyle y = 1 + \frac{ \sqrt{( 2\sqrt{5} - 2)(6 - 2\sqrt{5})^2}}{4}

y = 1 + 160 5 352 16 \large \displaystyle y = 1 + \frac{ \sqrt{160\sqrt{5} - 352}}{\sqrt{16} }

y = 1 + 10 5 22 \color{#20A900} \boxed{ \large \displaystyle y = 1 + \sqrt{10\sqrt{5} - 22} }

So:

a = 10 , b = 5 , c = 22 a + b + c = 37 \color{#3D99F6} \large \displaystyle a= 10, b = 5, c = 22 \rightarrow \boxed{\large \displaystyle a+b+c = 37}

Chew-Seong Cheong
Feb 19, 2020

Label the trapezoid as A B C D ABCD and altitude of the top vertex of the blue unit square as E F EF ; and let the angle a side of the blue square makes with the vertical be θ \theta as shown.

Then E F = sin θ + cos θ EF = \sin \theta + \cos \theta , D F = 1 + cos θ DF = 1 + \cos \theta , and D C = 1 + sin θ + cos θ DC=1+\sin \theta + \cos \theta , then

B C 1 E F 1 = D C D F B C = 1 + D C ( E F 1 ) D F Let B C = h h = 1 + ( sin θ + cos θ + 1 ) ( sin θ + cos θ 1 ) 1 + cos θ = 1 + 2 sin θ cos θ 1 + cos θ = 1 + 2 ( 2 sin θ 2 cos θ 2 ) ( 2 cos 2 θ 2 1 ) 1 + 2 cos 2 θ 2 1 = 1 + 2 sin θ 2 tan θ 2 Let t = tan θ 2 = 1 + 4 t 1 + t 2 2 t = 1 + 2 t ( 1 t 2 1 + t 2 See note: h is maximum, max ( h ) = 2 5 2 ( 3 5 ) 5 1 when t = 5 2 = 1 + 2 5 2 ( 3 5 ) ( 5 + 1 ) ( 5 1 ) ( 5 + 1 ) = 1 + 5 2 ( 5 1 ) = 1 + ( 5 2 ) ( 6 2 5 ) = 1 + 10 5 22 \begin{aligned} \frac {BC-1}{EF-1} & = \frac {DC}{DF} \\ \implies BC & = 1 + \frac {DC(EF-1)}{DF} & \small \blue{\text{Let }BC = h} \\ h & = 1 + \frac {(\sin \theta + \cos \theta +1 )(\sin \theta + \cos \theta -1)}{1+\cos \theta} \\ & = 1 + \frac {2\sin \theta \cos \theta}{1+\cos \theta} \\ & = 1 + \frac {2 \left(2 \sin \frac \theta 2 \cos \frac \theta 2\right)\left( 2\cos^2 \frac \theta 2-1\right)}{1+2\cos^2 \frac \theta 2-1} \\ & = 1 + 2 \sin \theta - 2\tan \frac \theta 2 & \small \blue{\text{Let }t = \tan \frac \theta 2} \\ & = 1 + \frac {4t}{1+t^2} - 2t \\ & = 1 + \frac {2t(1-t^2}{1+t^2} & \small \blue{\text{See note: }h \text{ is maximum,}} \\ \implies \max(h) & = \frac {2\sqrt{\sqrt 5-2}(3-\sqrt 5)}{\sqrt 5 -1} & \small \blue{\text{when }t = \sqrt{\sqrt 5-2}} \\ & = 1 + \frac {2\sqrt{\sqrt 5-2}(3-\sqrt 5)(\sqrt 5+1)}{(\sqrt 5 -1)(\sqrt 5 +1)} \\ & = 1 + \sqrt{\sqrt 5-2}(\sqrt 5-1) \\ & = 1 +\sqrt{(\sqrt 5-2)(6-2\sqrt 5)} \\ & = 1 + \sqrt{10 \sqrt 5-22} \end{aligned}

Therefore a + b + c = 10 + 5 + 22 = 37 a+b+c = 10 + 5 + 22 = \boxed {37} .


Note: To find max ( h ) \max(h) , we first find t t , when d h d t = 0 \dfrac {dh}{dt} = 0 .

d h d t = 4 ( 1 + t 2 ) 4 t ( 2 t ) ( 1 + t 2 ) 2 2 Equating to zero 4 4 t 2 ( 1 + t 2 ) 2 = 2 2 2 t 2 = t 4 + 2 t 2 + 1 t 4 + 4 t 2 1 = 0 t = 5 2 \begin{aligned} \frac {dh}{dt} & = \frac {4(1+t^2) - 4t(2t)}{(1+t^2)^2} - 2 & \small \blue{\text{Equating to zero}} \\ \implies \frac {4-4t^2}{(1+t^2)^2} & = 2 \\ 2-2t^2 & = t^4 + 2t^2 + 1 \\ t^4 + 4t^2 - 1 & = 0 \\ \implies t & = \sqrt{\sqrt 5 - 2} \end{aligned}

David Vreken
Feb 19, 2020

Draw in these lines and label the diagram as follows:

From right H C G \triangle HCG and G H = 1 GH = 1 , C G = sin θ CG = \sin \theta and C H = cos θ CH = \cos \theta . By symmetry, C G = H I = E J = F K = sin θ CG = HI = EJ = FK = \sin \theta and C H = E I = F J = G K = cos θ CH = EI = FJ = GK = \cos \theta .

A M E A N L \triangle AME \sim \triangle ANL by AA symmetry, so L N A N = E M A M \frac{LN}{AN} = \frac{EM}{AM} . Letting y = L K y = LK ,

  • L N = L K N K = y 1 LN = LK - NK = y - 1

  • A N = C D + C G + K G = sin θ + cos θ + 1 AN = CD + CG + KG = \sin \theta + \cos \theta + 1

  • E M = B I = C H + H I B C = sin θ + cos θ 1 EM = BI = CH + HI - BC = \sin \theta + \cos \theta - 1

  • A M = A B + B M = A B + E I = sin θ + 1 AM = AB + BM = AB + EI = \sin \theta + 1

Substituting these into the ratio gives y 1 sin θ + cos θ + 1 = sin θ + cos θ 1 sin θ + 1 \frac{y - 1}{\sin \theta + \cos \theta + 1} = \frac{\sin \theta + \cos \theta - 1}{\sin \theta + 1} which simplifies to y = 2 sin θ cos θ sin θ + 1 + 1 y = \frac{2 \sin \theta \cos \theta}{\sin \theta + 1} + 1 .

The maximum of y = L K y = LK occurs when the derivative y y' is zero, therefore, y = 2 ( 1 + sin θ ) ( cos 2 θ sin 2 θ ) 2 sin θ cos 2 θ ( sin θ + 1 ) 2 = 0 y' = \frac{2(1 + \sin \theta)(\cos^2 \theta - \sin^2 \theta) - 2 \sin \theta \cos^2 \theta}{(\sin \theta + 1)^2} = 0 . Using the identity cos 2 θ = 1 sin 2 θ \cos^2 \theta = 1 - \sin^2 \theta , this simplifies to ( sin θ + 1 ) ( sin 2 θ + sin θ 1 ) = 0 (\sin \theta + 1)(\sin^2 \theta + \sin \theta - 1) = 0 , which has one positive solution of sin θ = 5 1 2 \sin \theta = \frac{\sqrt{5} - 1}{2} .

This makes cos θ = 1 sin 2 θ = 5 1 2 \cos \theta = \sqrt{1 - \sin^2 \theta} = \sqrt{\frac{\sqrt{5} - 1}{2}} , which makes the maximum of L K LK to be y = 2 sin θ cos θ sin θ + 1 + 1 = 1 + 10 5 22 y = \frac{2 \sin \theta \cos \theta}{\sin \theta + 1} + 1 = 1 + \sqrt{10\sqrt{5} - 22} , so that a = 10 a = 10 , b = 5 b = 5 , c = 22 c = 22 , and a + b + c = 37 a + b + c = \boxed{37} .

It's interesting to see that the sides of H C G \triangle HCG end up being in a geometric progression with hints of the golden ratio.

David Vreken - 1 year, 3 months ago

Yeah, that is interesting. H G × H C = C G × C G HG \times HC = CG \times CG . Hmm....

Michael Mendrin - 1 year, 3 months ago

The only such right angled triangle (up to scaling). Seems weird it doesn't come up more often.

Chris Lewis - 1 year, 3 months ago

It is the equation for the golden ratio: x 2 + x = 1 x^2+x =1 . I just found out that it is called a Kepler triangle.

Maria Kozlowska - 1 year, 3 months ago

Is there any non-trig solution??

Sanchit Sharma - 4 months ago
Vinod Kumar
Apr 11, 2020

Let the angle of bottom left side of right square as x, determine the slope M(x) of inclined line of trapezoid: M=[{(2^0.5)sin(x+pi/4)-1}/{1+cos(x)-(2^0.5)cos(x+pi/4)}], and the vertical right side H of trapezoid: H=[1+{1+sin(x)+cos(x)}M]. Maximum of H(x) gives H=1+[10{(5)^0.5}-22]^0.5. Therefore, a+b+c=10+5+22 Answer=37

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...